Friday

March 6, 2015

March 6, 2015

Posted by **Shreya** on Saturday, January 7, 2012 at 12:54pm.

(15)(x-1) = (2x)(x+1)

2x^2-15x+17

do i put this in quadratic formula? i so confused.

- math-calculus -
**Steve**, Saturday, January 7, 2012 at 3:41pmFirst, get your simplification right:

(15)(x-1) = (2x)(x+1)

15x - 15 = 2x^2 + 2x

2x^2 - 13x + 15 = 0

You can use the quadratic formula, but it factors fairly easily:

(2x-3)(x-5) = 0

You can make it from there, I assume.

- math-calculus -
**Shreya**, Saturday, January 7, 2012 at 6:39pmthanks very much steve i got it :)

**Answer this Question**

**Related Questions**

Algebra - I need help trying to put the correct vocabulary words when solving ...

math-calculus - solve equation |x^2-2x-6| using quadratic formula. i not get how...

Algebra - I need help trying to put the correct vocabulary words when solving ...

calculus HS - Thanks for your help . I need to sketch the graph of f(x) = Sqrt 5...

Math - Use the quadratic formula to solve each of the following quadratic ...

Algebra - Solve the quadratic equation. 3x^2-15x+18=0 I know that the formula to...

math-calculus - i think i do something wrong again(2x+1)/(x-3)-(4x-1)/(2x-3) = 0...

math - (4.35E-2 - x)(7.56E-2 -x ) ============================ (0.324 + 2x)2 ...

math - Solve by elimination 5x+y=2 3x+y=1 This is what I got : 3(5x+y=2) -5(3x+y...

Math - Can you correct the errors? 4(x+3)=24 4(3x)=24 12x=24 12x/12= 24/12 X=2 5...